Lagrange interpolation


Recall from our basics discussion that a polynomial $\phi$ of degree $d$ is a vector of $d+1$ coefficients:

\begin{align} \phi &= [\phi_0, \phi_1, \phi_2, \dots, \phi_d] \end{align}

How to compute a polynomial’s coefficients from a bunch of its evaluations

Given $n$ pairs $(x_i, y_i)_{i\in[n]}$, one can compute or interpolate a degree $\le n-1$ polynomial $\phi(X)$ such that: \(\phi(x_i)=y_i,\forall i\in[n]\)

Specifically, the Lagrange interpolation formula says that: \begin{align} \label{eq:lagrange-formula} \phi(X) &= \sum_{i\in[n]} y_i \cdot \lagr_i(X),\ \text{where}\ \lagr_i(X) = \prod_{j\in[n],j\ne i} \frac{X-x_j}{x_i-x_j} \end{align}

This formula is intimidating at first, but there’s a very simple intuition behind it. The key idea is that $\lagr_i(X)$ is defined so that it has two properties:

  1. $\lagr_i(x_i) = 1,\forall i\in[n]$
  2. $\lagr_i(x_j) = 0,\forall j \in [n]\setminus\{i\}$

You can actually convince yourself that $\lagr_i(X)$ has these properties by plugging in $x_i$ and $x_j$ to see what happens.

Important: The $\lagr_i(X)$ polynomials are dependent on the set of $x_i$’s only (and thus on $n$)! Specifically each $\lagr_i(X)$ has degree $n-1$ and has a root at each $x_j$ when $j\ne i$! In this sense, a better notation for them would be $\lagr_i^{[x_i, n]}(X)$ or $\lagr_i^{[n]}(X)$ to indicate this dependence.

Example: Interpolating a polynomial from three evaluations

Consider the following example with $n=3$ pairs of points. Then, by the Lagrange formula, we have:

\[\phi(X) = y_1 \lagr_1(X) + y_2 \lagr_2(X) + y_3 \lagr_3(X)\]

Next, by applying the two key properties of $\lagr_i(X)$ from above, you can easily check that $\phi(x_i) = y_i,\forall i\in[3]$: \begin{align} \phi(x_1) &= y_1 \lagr_1(x_1) + y_2 \lagr_2(x_1) + y_3 \lagr_3(x_1) = y_1 \cdot 1 + y_2 \cdot 0 + y_3 \cdot 0 = y_1\\
\phi(x_2) &= y_1 \lagr_1(x_2) + y_2 \lagr_2(x_2) + y_3 \lagr_3(x_2) = y_1 \cdot 0 + y_2 \cdot 1 + y_3 \cdot 0 = y_2\\
\phi(x_3) &= y_1 \lagr_1(x_3) + y_2 \lagr_2(x_3) + y_3 \lagr_3(x_3) = y_1 \cdot 0 + y_2 \cdot 0 + y_3 \cdot 1 = y_3 \end{align}

An important detail is that the degree of the interpolated $\phi(X)$ is $\le n-1$ and not necessarily exactly equal to $n-1$. To see this, consider interpolating the polynomial $\phi(X)$ such that $\phi(i) = i$ for all $i\in [n]$. In other words, $x_i = y_i = i$.

The inspired reader might notice that the polynomial $\phi(X) = X$ could satisfy our constraints. But is this what the Lagrange interpolation will return? After all, the interpolated $\phi(X)$ is a sum of degree $n-1$ polynomials $\lagr_i(X)$, so could it have degree 1? Well, it turns out, yes, because things cancel out. To see this, take a simple example, with $n=3$: \begin{align} \phi(X) &=\sum_{i\in [3]} i \cdot \lagr_i(X) = \sum_{i\in [3]} i \cdot \prod_{j\in[3]\setminus{i}} \frac{X - j}{i - j}\\
&= 1\cdot \frac{X-2}{1-2}\frac{X-3}{1-3} + 2\cdot \frac{X-1}{2-1}\frac{X-3}{2-3} + 3\cdot\frac{X-1}{3-1}\frac{X-2}{3-2}\\
&= \frac{X-2}{-1}\frac{X-3}{-2} + 2\cdot \frac{X-1}{1}\frac{X-3}{-1} + 3\cdot \frac{X-1}{2}\frac{X-2}{1}\\
&= \frac{1}{2}(X-2)(X-3) - 2(X-1)(X-3) + \frac{3}{2}(X-1)(X-2)\\
&= \frac{1}{2}[(X-2)(X-3) + 3(X-1)(X-2)] - 2(X-1)(X-3)\\
&= \frac{1}{2}[(X-2)(4X-6)] - 2(X-1)(X-3)\\
&= (X-2)(2X-3) - 2(X-1)(X-3)\\
&= (2X^2 - 4X - 3X + 6) - 2(X^2 - 4X +3)\\
&= (2X^2 - 7X + 6) - 2X^2 + 8X - 6\\
&= X \end{align}

Computational overhead of Lagrange interpolation

If done naively, interpolating $\phi(X)$ using the Lagrange formula in Equation \ref{eq:lagrange-formula} will take $O(n^2)$ time.

However, there are known techniques for computing $\phi(X)$ in $O(n\log^2{n})$ time. We described part of these techniques in a previous blog post, but for the full techniques please refer to the “Modern Computer Algebra” book1.

  1. Fast polynomial evaluation and interpolation, by von zur Gathen, Joachim and Gerhard, Jurgen, in Modern Computer Algebra, 2013